Underground ice in permafrost, Mackenzie Delta-Tuktoyaktuk Peninsula, N.W.T. ... - Gell, William Alan (University of British Columbia, 2010)
A study was made of the petrology of a variety of underground ice types in permafrost on the Tuktoyaktuk Peninsula and Pelly Island, Mackenzie Delta, N.W.T. Ice bodies of a considerable range of ages occur, including some deformed in the Wisconsin glaciation; also permafrost and ice is growing ab initio beneath recently drained lake bottoms. The spectrum of ice body size is also wide, extending from pore-sized particles to beds 25 m thick. The major objective of the study was an understanding of the growth and deformation of such ice bodies from a petrologic viewpoint. Thus several bodies of known, recent, age -were analyzed in order to enumerate features typical of growth. This was possible for icing mounds, tension cracks and active layer ice which grew in winter 1973-74. Growth conditions were inferred in terms of water supply, freezing directions and rates, solute rejection (bubble formation) and crystal size, shape, lattice and dimensional orientation. On the basis of this knowledge of growth features, ...